Different levels of fertilization with 4-14-8 formula on profit and risk of commercial potato production - Crisostomo, Lindbergue Araujo; Campos, Tarcísio Gomes da Silva; Cordeiro, Célia Maria Torres; Castor, Otoniel Soares (Pesquisa Agropecuaria Brasileira, 2014)
A two-year field study 1980 and 1981 at the Centro Nacional de Pesquisa de Hortaliças in Brasília, DF., Brazil, was carried out on a Red-Latosol clay soil, envolving five levels (0, 2, 4, 6 and 8 t/ha) of 4-14-8 commercial fertilizer mixture and three potato cultivars (Achat, Aracy and Bintje). The experimental design was a randomized block, with four replications, in a 5 x 3 factorial arrangement. The yield of marketable tubers, cultivars and the combinations of these two factors have shown statistically significant differences. The yield for each year and cultivar combination presented a good fit using Mitscherlich’s equation. The best technological alternatives in terms of profit and risk were selected using stochastic dominance rules for each cultivar and among these cultivars.